MyGuide long COVID: An online self-management tool for people with long COVID - Hiten Naik; Kyla Pongratz; Michelle Malbeuf; Sonya Kung; Lori Last; Asuka Sugiyama; Esther Khor; Marlee McGuire; Adeera Levin; Karen C. Tran (Internet Interventions)
Background: Long COVID is a relatively new condition for which patients are asked to employ self-management strategies to manage their symptoms. However, it can be challenging for individuals with long COVID to find reliable and actionable self-management resources. The objective of this project was to develop an online tool for individuals with long COVID that is patient-centered, accessible, and customizable to meet individual needs. Methods: MyGuide Long COVID (www.longCOVIDguide.ca) was developed in British Columbia (BC), Canada, by a team that included long COVID clinicians and patient partners. Site visitors answer questions about their symptoms, and MyGuide generates a curated set of self-management resources tailored to their needs. Since its launch in August 2023, Google Analytics has been used to monitor website activity. Results: Within the first year, MyGuide had 52,578 total page views and 8570 new users. The most popular method to access MyGuide was by computer (56.3 % of users), and the most represented city was Vancouver, BC (23.5 % of users). The most popular topics were “Post Exertional Malaise” (1339 sessions) and “What is long COVID?” (1257 sessions). Conclusions: An online tool to support chronic disease self-management can be successfully co-developed with patient partners and engagement tracked using web analytics.